(untitled) - Sahelian, Ray (New York, 1996)
A hormone called DHEA (dehydroepiandrosterone), which is produced by the adrenal glands, is now available without a prescription. Researchers claim that DHEA is a means to boosting sex drive, enhancing energy, mood, and memory, and improving the immune system. Further to its credit, it has been touted as an aid to weight loss and a way to increase muscle mass. Additionally, DHEA is being used as a treatment for autoimmune disorders, cancer, heart disease, and osteoporosis. However, author Dr. Ray Sahelian maintains it is a more complex issue and that you should be well-informed if planning to take this hormone. He provides straightforward answers regarding the benefits and limitations of this vital and important supplement. In DHEA: A Practical Guide, Dr. Sahelian discusses the safety of DHEA, how DHEA affects the brain, heart, and immune system, DHEA levels throughout life, and what is known about DHEA's anti-aging potential. He covers, in-depth, the practical aspects of how much to take and when, and even includes personal stories of DHEA users. His clear and concise style makes it easy to learn anything one might want to know about DHEA.
Keywords: Dehydroepiandrosterone,Dehydroepiandrosterone; Công trình phổ biến,Popular works